Analisis Faktor Perubahan Iklim terhadap Hasil Panen pada Sayuran di Kabupaten Enrekang, Sulawesi Selatan - Zahra, Alifah; Hayyan, M. Athaya; Akifurahman, Syauki; Naufal, Rifki (Seminar Nasional Lahan Suboptimal, 2023)
Zahra, A., Hayyan, M. A., Akifurahman, S., & Naufal, R. (2023). Analysis of climate change factors on the number of yields in vegetable crops in Enrekang Regency, South Sulawesi. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang  21 Oktober 2023. (pp. 558-563).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The impact of climate change on vegetable crop production in Enrekang District, South Sulawesi, has become a global concern. This study aims to identify the influence of climate variability (rainfall, air temperature, and wind direction) on the production of vegetables such as mustard, tomatoes, carrots, and chickpeas. Horticultural production data is obtained from the Agriculture Office of Enrekang Regency and South Sulawesi, while weather condition data is taken from the Meteorology, Climatology and Geophysics Agency. This data was then analyzed using regression and correlation methods using SPSS statistical software. The results showed a significant effect of climate variability on tomato and chickpea production, while mustard greens and carrots tended to be unaffected. This is indicated by a significance value (p-value) greater than 0.05. The significance values for rainfall to the production of the three crops were 0.784, 0.813, and 0.042, respectively, while for air temperature were 0.724, 0.383, and 0.098. The findings emphasize the need for agricultural adaptation and the development of climate-resistant varieties. The research provides important insights into the impact of climate change on vegetable crop production in the region.